2016
DOI: 10.3892/ijo.2016.3740
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of the triggering receptor expressed on myeloid cells 2 inhibits progression of renal cell carcinoma via regulating related protein expression and PTEN-PI3K/Akt pathway

Abstract: The triggering receptor expressed on myeloid cells 2 (TREM-2) is suggested to be involved in the development of certain human malignancies. However, the functions of TREM-2 in renal cell carcinoma (RCC) are still less known. To reveal the effects of TREM-2 on the RCC progression, we examined the TREM-2 expression in RCC tumor tissues. Then, we analyzed the cell proliferation, cell apoptosis, cell cycle and expression of the relative factors in two selected RCC cell lines post RNA interference. We also analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
(45 reference statements)
3
20
0
Order By: Relevance
“…Our RNA sequencing studies with TRIP13 knockdown cells identified downstream molecular targets, including COL6A3 (collagen/extracellular matrix), TREM2 (inflammation), SHC3 (MVP/MEK/ERK activation), and KLK7 (MAPK signaling). Prior studies have implicated these TRIP13 targets in the progression of various cancers, including COL6A3 [44,45] and KLK7 [46] in CRCs, SHC3 in hepatocellular carcinomas [47], and TREM2 in gastric cancers [48] and renal cell carcinomas [49]. Our findings were validated with human samples, which showed upregulation of COL6A3, KLK7, TREM2, and SHC3 in CRCs compared to matched normal colon tissues.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our RNA sequencing studies with TRIP13 knockdown cells identified downstream molecular targets, including COL6A3 (collagen/extracellular matrix), TREM2 (inflammation), SHC3 (MVP/MEK/ERK activation), and KLK7 (MAPK signaling). Prior studies have implicated these TRIP13 targets in the progression of various cancers, including COL6A3 [44,45] and KLK7 [46] in CRCs, SHC3 in hepatocellular carcinomas [47], and TREM2 in gastric cancers [48] and renal cell carcinomas [49]. Our findings were validated with human samples, which showed upregulation of COL6A3, KLK7, TREM2, and SHC3 in CRCs compared to matched normal colon tissues.…”
Section: Discussionsupporting
confidence: 77%
“…Genes modulated by TRIP13 knockdown included COL6A3, KLK7, TREM2, and SHC3. COL6A3 [44,45] and KLK7 [46] in CRCs, SHC3 in hepatocellular carcinomas [47], and TREM2 in gastric cancers [48] and renal cell carcinomas [49] are associated with tumor growth. We showed decreased mRNA expression of COL6A3, KLK7, TREM2, and SHC3 after TRIP13 knockdown in CRC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al showed high TREM-2 expression in renal cell carcinoma. Knockdown of TREM-2 inhibited cell growth and induced cell cycle arrest and apoptosis of tumor cells [ 48 ]. On the contrary, in a recent study from 2019, Tang et al described TREM-2 as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from HCC, TREM2 has also been studied in many other tumors, such as colorectal carcinoma, lung cancer, and glioma [124][125][126][127][128]. However, it remains to be explored whether the mechanism of TREM2 in liver tumors and other tumors is consistent.…”
Section: Roles Of Trem In Liver Tumorigenesismentioning
confidence: 99%